Effect of deep cryogenic treatment on the microstructure and mechanical properties of AlCrFe2Ni2 High-entropy alloy - Chengze Li; Yingdong Qu; Yufeng Zhang; Qingyao Lv; Hao Qi (Materials Research Express, 2020)
The influence of deep cryogenic treatment on the microstructure and properties of AlCrFe _2 Ni _2 high-entropy alloy were studied by examining its phase composition, microstructure, and properties after cryogenic treatment. The results showed that as the cryogenic treatment increased, the alloy was composed of face-centered cubic (FCC) and body-centered cubic (BCC) phases. As the treatment time increased, the grain orientation of the BCC phase and B2 phase changed and transformed into each other, and the band FCC phase structures became shorter and more disordered. Deep cryogenic treatment effectively improved the hardness, yield strength, and wear resistance of the alloy. The alloy displayed the best performance with a holding time of 4 h, and the Vickers hardness (338 HV) was 11.6% higher than the as-cast alloy, and the yield strength (920 MPa) was 22.7% higher. The friction coefficient was 0.643, and the wear resistance was also significantly improved.